Bioremediation of coastal aquaculture effluents spiked with florfenicol using microalgae-based granular sludge – a promising solution for recirculating aquaculture systems. (15th April 2023) - Oliveira, Ana S.; Alves, Marta; Leitão, Frederico; Tacão, Marta; Henriques, Isabel; Castro, Paula M.L.; Amorim, Catarina L.
Highlights: Microalgae-based granules able to efficiently treat coastal aquaculture streams. Stable granules were quickly formed, accompanied by increased EPS production. Sporadic presence of florfenicol did not disrupt the system removal performance. Treated effluent complying with aquaculture water recirculation parameters. Microbial community dynamic in composition but with stable performance. Abstract: Aquaculture is a crucial industry in the agri-food sector, but it is linked to serious environmental problems. There is a need for efficient treatment systems that allow water recirculation to mitigate pollution and water scarcity. This work aimed to evaluate the self-granulation process of a microalgae-based consortium and its capacity to bioremediate coastal aquaculture streams that sporadically contain the antibiotic florfenicol (FF). A photo-sequencing batch reactor was inoculated with an autochthonous phototrophic microbial consortium and was fed with wastewater mimicking coastal aquaculture streams. A rapid granulation process occurred within ca. 21 days, accompanied by a substantially increase of extracellular polymeric substances in the biomass. The developed microalgae-based granules exhibited high and stable organic carbon removal (83-100%). Sporadically wastewater contained FF which was partially removed (ca. 5.5-11.4%) from the effluent. In periods of FF load, the ammonium removal slightly decreased (from 100 to ca. 70%), recovering 2 days after FF feeding ceased. A high-chemical quality effluent was obtained, complying with ammonium, nitrite, and nitrate concentrations for water recirculation within a coastal aquaculture farm, even during FF feeding periods. Members belonging to the Chloroidium genus were predominant in the reactor inoculum (ca. 99%) but were replaced from day-22 onwards by an unidentified microalga from the phylum Chlorophyta (>61%). A bacterial community proliferated in the granules after reactor inoculation, whose composition varied in response to feeding conditions. Bacteria from the Muricauda and Filomicrobium genera, Rhizobiaceae, Balneolaceae, and Parvularculaceae families, thrived upon FF feeding. This study demonstrates the robustness of microalgae-based granular systems for aquaculture effluent bioremediation, even during periods of FF loading, highlighting their potential as a feasible and compact solution in recirculation aquaculture systems. Graphical abstract: Image, graphical abstract